CURRENT PRINCIPLES OF DIAGNOSIS AND TREATMENT OF BONE LESIONS IN PATIENTS WITH DIABETIC FOOT SYNDROME - Prykhidko, R.A.; Krasnov, O.H.; Dudchenko, M.O.; Kravtsiv, M.I.; Zaiets, S.M.; Ivashchenko, D.M.; Krasnova, O.I. (World of Medicine and Biology, 2024)
One of the most unresolved issues in patients with diabetic foot syndrome is the diagnosis and treatment of bone tissue lesion. The aim was to compare the results of treatment of bone tissue lesions in patients with diabetic foot syndrome and to highlight the factors of prevention of limb amputation. We have carried out treatment of 658 patients with diabetic foot syndrome. High amputation of lower limb in the control group were performed more often. Mortality was higher in the control group. At the same time, the supporting function of the foot in patients was preserved more often in the main group. Radical surgical treatment of osteomyelitis leads to a reduction in the duration of treatment of patients with diabetic foot syndrome and an increase in the number of surgical interventions. However, conservative therapy of osteomyelitis reduces the risk of impaired foot support function and high amputation of the lower limb.